Seed germination and early seedling survival of the invasive species Prosopis juliflora (Fabaceae) depend on habitat and seed dispersal mode in the Caatinga dry forest - Nascimento,Clóvis Eduardo de Souza; da Silva,Carlos Alberto Domingues; Leal,Inara Roberta; Tavares,Wagner de Souza; Serrão,José Eduardo; Zanuncio,José Cola; Tabarelli,Marcelo (PeerJ, 2020)
Background Biological invasion is one of the main threats to tropical biodiversity and ecosystem functioning. Prosopis juliflora (Sw) DC. (Fabales: Fabaceae: Caesalpinioideae) was introduced in the Caatinga dry forest of Northeast Brazil at early 1940s and successfully spread across the region. As other invasive species, it may benefit from the soils and seed dispersal by livestock. Here we examine how seed dispersal ecology and soil conditions collectively affect seed germination, early seedling performance and consequently the P. juliflora invasive potential. Methods Seed germination, early seedling survival, life expectancy and soil attributes were examined in 10 plots located across three habitats (flooding plain, alluvial terrace and plateau) into a human-modified landscape of the Caatinga dry forest (a total of 12,000 seeds). Seeds were exposed to four seed dispersal methods: deposition on the soil surface, burial in the soil, passed through cattle (Boss taurus) digestive tracts and mixed with cattle manure and passed through mule (Equus africanus asinus × Equus ferus caballus) digestive tracts and mixed with mule manure. Seeds and seedlings were monitored through a year and their performance examined with expectancy tables. Results Soils differed among habitats, particularly its nutrient availability, texture and water with finely-textured and more fertile soils in the flooding plain. Total seed germination was relatively low (14.5%), with the highest score among seeds buried in the flooding plain (47.4 ± 25.3%). Seed dispersal by cattle and mule also positively impacted seed germination. Early seedling survival rate of P. juliflora was dramatically reduced with few seedlings still alive elapsed a year. Survival rate was highest in the first 30 days and declined between 30 and 60 days with stabilization at 70 days after germination in all seed treatments and habitats. However, survival and life expectancy were higher in the flooding plain at 75 days and lower in the plateau. Prosopis juliflora seedling survival and life expectancy were higher in the case seeds were mixed with cattle manure. Synthesis Prosopis juliflora seeds and seedlings are sensitive to water stress and habitat desiccation. Therefore, they benefit from the humid soils often present across human-disturbed flooding plains. This plant also benefits from seed deposition/dispersal by livestock in these landscapes, since cattle manure represents a nutrient-rich and humid substrate for both seeds and seedlings. The quality of the seed dispersal service varies among livestock species, but this key mutualism between exotic species is due to the arillate, hard-coated and palatable seeds. Prosopis juliflora traits allow this species to take multiple benefits from human presence and thus operating as a human commensal.
Keywords: Alluvial terrace; Mesquite; Plateau; Manure; Caesalpinioideae; Seed dormancy; River bank; Expectancy table; Population; Flooding plain